2015
DOI: 10.1128/jvi.03156-14
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between TIM-1 and NPC1 Is Important for Cellular Entry of Ebola Virus

Abstract: Multiple host molecules are known to be involved in the cellular entry of filoviruses, including Ebola virus (EBOV); T-cell immunoglobulin and mucin domain 1 (TIM-1) and Niemann-Pick C1 (NPC1) have been identified as attachment and fusion receptors, respectively. However, the molecular mechanisms underlying the entry process have not been fully understood. We found that TIM-1 and NPC1 colocalized and interacted in the intracellular vesicles where EBOV glycoprotein (GP)-mediated membrane fusion occurred. Intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
75
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 51 publications
1
75
1
1
Order By: Relevance
“…KIM-1 is a cell surface receptor in epithelial and lymphoid/myeloid cells. It behaves as a scavenger receptor for oxidized LDL and phosphatidylserine and as Ebola and Hepatitis A virus entry receptor in epithelial cells [2] . Kim-1 binding to phosphatidylserine allows the phagocytosis of apoptotic cells.…”
Section: Kidney Injury Moleculementioning
confidence: 99%
See 1 more Smart Citation
“…KIM-1 is a cell surface receptor in epithelial and lymphoid/myeloid cells. It behaves as a scavenger receptor for oxidized LDL and phosphatidylserine and as Ebola and Hepatitis A virus entry receptor in epithelial cells [2] . Kim-1 binding to phosphatidylserine allows the phagocytosis of apoptotic cells.…”
Section: Kidney Injury Moleculementioning
confidence: 99%
“…As an example, kidney injury in non-albuminuric CKD (e.g. certain tubulointerstitial and vascular nephropathies) is not represented in the glomerular-based risk categorization until eGFR falls <60 ml/ min/1.73 m 2 . Tubular injury markers may be better suited for risk categorization in early stages in these patients.…”
mentioning
confidence: 99%
“…It has been demonstrated that EBOV GP-mediated viral entry consists of at least five steps, including cell surface attachment, endocytosis, cathepsin cleavage of GP, fusion receptor binding, and membrane fusion (32)(33)(34)(35). The results of the time-of-addition assay in Fig.…”
Section: Fig 3 Ex Vivomentioning
confidence: 99%
“…The use of PVs has been of crucial significance in the rapid pace of research into the Middle Eastern Respiratory syndrome (MERS) outbreak [8][9][10][11]. During the recent Ebola outbreak, PVs were successfully used in high-throughput screening studies that helped in the identification of potential antivirals and filovirus entry inhibitors [12][13][14] as well as in the study of the viral life cycle and virus receptor interaction [15].…”
Section: Pvs For Research and Therapeutic Agent Screeningmentioning
confidence: 99%